2006
DOI: 10.1007/s11079-006-6811-8
|View full text |Cite
|
Sign up to set email alerts
|

The International Business Cycle in a Changing World: Volatility and the Propagation of Shocks in the G-7

Abstract: The changing relationships between the G-7 countries are examined through VAR models for quarterly growth, estimated over sub-periods and using a rolling data window. Trivariate models are employed, each including the US and a European (E15) aggregate. The results show that conditional volatility of growth has declined relatively more since 1980 for E15 than for the US, aggregate European shocks have increased impact on “core†European countries from around 1980, the effects of the US on Europe are largest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
4
15
0
Order By: Relevance
“…As shown by the close correspondence between the dotted and dashed lines, there is little difference in the transmission of U.S. shocks to other regions when the magnitude of shocks is held constant. The ''great moderation'' in U.S. macroeconomic volatility cuts U.S. spillovers to other regions by a half, but the response of the other economies to a U.S. shock of a given size has remained relatively constant, consistent with the findings of Stock and Watson (2005) and Perez, Osborn, and Artis (2006).…”
Section: Results By Subsamplesupporting
confidence: 78%
See 1 more Smart Citation
“…As shown by the close correspondence between the dotted and dashed lines, there is little difference in the transmission of U.S. shocks to other regions when the magnitude of shocks is held constant. The ''great moderation'' in U.S. macroeconomic volatility cuts U.S. spillovers to other regions by a half, but the response of the other economies to a U.S. shock of a given size has remained relatively constant, consistent with the findings of Stock and Watson (2005) and Perez, Osborn, and Artis (2006).…”
Section: Results By Subsamplesupporting
confidence: 78%
“…The basic VARs contain GDP growth for each of the four regions. Four lags were used in the VAR, following Perez, Osborn, and Artis (2006) and Stock and Watson (2005). 5 A major focus of the empirical analysis is examining the robustness of the results to alternative orderings of the contemporaneous correlations across shocks in the VAR.…”
Section: How Large Are Spillovers?mentioning
confidence: 99%
“…Also, Osborn et al (2005) argued that the US growth rates have positive and significant impacts on Germany, Italy and the UK. Perez, Osborn, and Artis (2003) found that the US economy leads the German economy.…”
Section: Empirical Analysismentioning
confidence: 99%
“…Crucini et al (2008 also obtain that G7 shocks have the highest share (80 percent) in output growth variance of France among the G7 countries. Finally, the country-specific shocks have only a limited share in the output growth variance of France, while US and (even much more) EU15 shocks have large weights in that variance according to the findings of Perez et al (2006). Note that there are important differences between our empirical approach and the empirical approach of the aforementioned studies.…”
Section: Discussionmentioning
confidence: 93%
“…2 This approach alone 1 Stock and Watson (2005) and Canova et al (2007) estimate, for example, common shocks and countryspecific shocks with spillover effects within the G7 group. Perez et al (2006) identify US, EU15 and countryspecific shocks. Crucini et al (2008) model common G7, nation-specific and idiosyncratic factors.…”
Section: Introductionmentioning
confidence: 99%